Corporate Value as a Function of Firm Revenue Base among Nigerian Food and Beverages Firms - Kelvin Ibobo; Hilary Muojekwu; Gilbert Ogechukwu Nworie (PT ARRUS Intelektual Indonesia, 2026)
This study examined the effect of firm revenue base on the corporate value of listed food and beverage firms in Nigeria, using market value added as the measure of corporate value. The study adopted an ex-post facto research design and relied on secondary data obtained from the annual reports and financial statements of twelve purposively selected firms listed on the Nigerian Exchange Group between 2012 and 2024. Panel estimated generalised least squares regression analysis were used to analyze the data. The findings revealed that firm revenue base has a significant and positive effect on market value added at 5% significance level, indicating that increases in revenue enhance the corporate value of firms (? = 0.762651; p = 0.0000). In conclusion, firms with stable and growing revenue streams are better positioned to generate shareholder wealth. The study recommends that management should implement aggressive but sustainable revenue expansion strategies, such as product diversification, market penetration, and pricing optimization, and also give a special attention to data-driven marketing, customer retention programs, and investments in efficient distribution channels, as these initiatives can significantly boost revenue while controlling operational costs.